2019
DOI: 10.1371/journal.pone.0210541
|View full text |Cite
|
Sign up to set email alerts
|

Dog-bite injuries in Korea and risk factors for significant dog-bite injuries: A 6-year cross-sectional study

Abstract: Introduction An accurate understanding of the current status of dog-bite injuries in Korea is essential for establishing preventive strategies. There have been no national reports about dog-bite injuries in Korea. This study investigated dog-bite injuries in Korea that were registered in the nationwide injury surveillance database and analysed the risk factors for significant dog-bite injury. Methods A multicentre cross-sectional study was conducted using the emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
19
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 18 publications
(18 reference statements)
12
19
2
1
Order By: Relevance
“…This might have led to increased interaction with dogs and hence an increase in dog bite cases during the months following winter. A somewhat similar trend has been reported from Iran and Korea [17,25]; Park et al [25], however, relate it to the length of the day. However, in a five-year study from Srilanka, Kularatne et al reported a more or less even pattern across seasons [20].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 77%
“…This might have led to increased interaction with dogs and hence an increase in dog bite cases during the months following winter. A somewhat similar trend has been reported from Iran and Korea [17,25]; Park et al [25], however, relate it to the length of the day. However, in a five-year study from Srilanka, Kularatne et al reported a more or less even pattern across seasons [20].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 77%
“…No clear pattern of seasonality was found, however our results showed that more cases of injuries were declared during the months of May and August, similar findings have been previously reported (47,53). One hypothesis is that contacts with dogs increase during the long photoperiod season, especially since dogs are usually kept outside in Nunavik (43).…”
Section: Contextsupporting
confidence: 92%
“…Men in northern communities traditionally practice such activities during fall or winter. The association between age and gender has been mentioned in other studies (16,47,48), however the patterns seem to be different depending on the social environment and the related risk factors as illustrated by the current study. This finding sustains the need to tailor a specific prevention program to this unique profile.…”
Section: Contextsupporting
confidence: 67%
“…Men in northern communities traditionally practice such activities during fall or winter. This association with age and gender has been mentioned in other studies (17,48,49); however, the pattern seems to vary depending on social environment and related risk factors, as illustrated in our study.…”
Section: Exploring Patterns Of Potential Human Exposure To Rabiessupporting
confidence: 86%